Переваги та особливості впровадження автоматизованих систем управління інженерним обладнанням в готелях - Павлюченко, Олена Станіславівна; Зубрицька, А.; Близнюк, Юлія Сергіївна (My University, 2013)
This article explores the nature of the building management systems (BMS) and its using in hotels. Author highlighted the main advantages that get hotels from using of such systems. BMS system allow annually save up to 20% of the cost of electricity, heat and water supply of the building and pay off for itself in the 5th year of its operation. And after six year exploitation it starts to pay the owners an additional 7-5% of the net annual profits of all operating costs.
Keywords: system room management system; hotel; система управління будівлею; готель; кафедра технології ресторанної і аюрведичної продукції